1999
DOI: 10.1002/(sici)1520-6327(1999)41:1<42::aid-arch7>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ecdysteroid action of ring‐substituted dibenzoylhydrazines in Spodoptera exigua

Abstract: Ring-substituted dibenzoylhydrazines are well known as nonsteroidal ecdysone agonists that cause precocious larval molt leading to death. Among them, tebufenozide (RH-5992) is used in practice as insecticide to control lepidopteran pests selectively. Recently, a new dibenzoylhydrazine, methoxyfenozide (RH-2485), with a higher activity for Lepidoptera, has been discovered. To obtain insight into the molecular mechanisms involved in the insecticidal selectivity of the dibenzoylhydrazine family, we measured the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…This may be because of the facile oxidation of the sulfide moiety to sulfone/sulfoxide through metabolism. We reported that RH-5849 was 10-fold less toxic than tebufenozide against Lepidopteran C. suppressalis (Pyralidae; pLD50 = 6.27 vs. 7.32) and 100-fold less toxic than tebufenozide against S. exigua (Noctuidae; pLD50 = 4.91 vs. 7.06) [40]. The difference in pLD50 values between RH-5849 and tebufenozide was 100-fold against S. litura (Noctuidae), which is consistent with the toxicity results for S. exigua.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of the facile oxidation of the sulfide moiety to sulfone/sulfoxide through metabolism. We reported that RH-5849 was 10-fold less toxic than tebufenozide against Lepidopteran C. suppressalis (Pyralidae; pLD50 = 6.27 vs. 7.32) and 100-fold less toxic than tebufenozide against S. exigua (Noctuidae; pLD50 = 4.91 vs. 7.06) [40]. The difference in pLD50 values between RH-5849 and tebufenozide was 100-fold against S. litura (Noctuidae), which is consistent with the toxicity results for S. exigua.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, RH-2485 was found to have a high accumulation rate in target cells and high binding affinity to ecdysteroid receptors in Lepidoptera compared with ecdysteroids (Yund and Osterbur, 1985;Smagghe et al, 1999Smagghe et al, , 2001a.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…Methoxyfenozide (RH-2485) is the latest compound in this class to be developed commercially and is the most potent analog to date against larval Lepidoptera (Ishaaya et al 1995;Le et al 1996;Trisyono and Chippendale 1997;Smagghe et al 1998bSmagghe et al , 1999. The Þrst sales of methoxyfenozide occurred in 1999, and the Þrst full registrations in the United States were granted for cotton and pome fruits in 2000.…”
mentioning
confidence: 99%